The Impact of Customer Relationship Management on Tourist Satisfaction in Movenpick Resort and Residences in Aqaba, Jordan - Mohammad Ragab Khashman Al-Laymoun (European Scientific Journal, ESJ, 2016)
This study aims at investigating the impact of customer relationship management on tourist satisfaction in Movenpick Resort and Residences in Aqaba, Jordan. In this research, the Statistical Package for Social Sciences (SPSS) was used for data entry as well as for examining the data. Data preparation was the initial step. It aimed to convert raw data into a more structured format that is more appropriate for analysis. The results show that there is a significant relationship between Marketing activities and tourist satisfaction about the service provided in Movenpick Resort and Residences in Aqaba, Jordan.